Lelé: architecture, urbanism and engineering towards the reconstruction of popular neighbourhoods (ARQUISUR Revista, 2017)
Remembered for his contribution as an architect and builder, João Filgueiras Lima (1932-2014) also left a legacy of urban studies from his work in Salvador, Abadiânia and Rio de Janeiro throughout the 1980s. Taking as a theoretical reference the writings of Portuguese architect and urbanist Nuno Portas, this article analyzes the different natures of Lelé's action on cities, moving between varied scales of design to integrate decisions that transformed architecture and technology into supporting tools towards a pioneering consolidation of popular neighborhoods, even during the military dictatorship. For this, we use a wide bibliographical review, interviews, field activities and archival research that support a doctoral thesis in the stage of completion and that aim, among others, to identify new directions of development and application for technologies of pre-fabrication and architecture industrialization Transformation of Brazilian cities.
Keywords: ferrocement; selfbuild; prefabrication; technical assistance; technology